Financial ratios and stock prices: Unraveling the dynamics in Indonesia's industrial and consumer staples sectors - Tasyahadul Fadlatil Laili (Universitas Muhammadiyah Malang, 2024)
Purpose: This study examines the effect of financial ratios consisting of ROA, ROE, CR, PER and EPS on stock prices. Methodology/approach: The data analysis technique used is descriptive analysis and multiple linear regression analysis. Findings: The results of this study indicate that ROE, PER, and EPS have a significant positive effect on stock prices. While the ROA and CR variables do not have a partial effect on stock prices. Practical implications: To understanding the impact of financial ratios on stock prices provides valuable insights into investment strategies. Investors can use the findings to make informed decisions to maximize potential returns. Originality/value: The originality and value of this study lie in its comprehensive analysis of financial ratios (ROA, ROE, CR, PER, and EPS) and their specific impact on stock prices. The study's focus on the Industrial and Consumer Staples sectors in Indonesia during 2017-2021 adds unique insights.